2021
DOI: 10.3390/diagnostics11050846
|View full text |Cite
|
Sign up to set email alerts
|

Blood Procalcitonin Level as a Diagnostic Marker of Pediatric Bacterial Meningitis: A Systematic Review and Meta-Analysis

Abstract: Early diagnosis and treatment of bacterial meningitis in children are essential, due to the high mortality and morbidity rates. However, lumbar puncture is often difficult, and cerebrospinal fluid (CSF) culture takes time. This meta-analysis aims to determine the diagnostic accuracy of blood procalcitonin for detecting bacterial meningitis in children. We conducted a systematic search on electronic databases to identify relevant studies. Pooled sensitivity, specificity, and diagnostic odds ratio (DOR) were cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 57 publications
0
7
0
2
Order By: Relevance
“…Previous studies showed that blood levels of acute phase reactants CRP and procalcitonin were helpful in differentiation of CNS infection and specifically bacterial meningitis from other disorders. 22 , 31 , 32 However, these studies were not performed in the whole population of patients with suspected CNS infection and did not include patients with systemic infections without CNS involvement, where acute phase reactants are also elevated. Our results indicate that inflammatory markers in blood have a limited diagnostic value in the diagnosis of CNS infection and these cannot be used to exclude this.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that blood levels of acute phase reactants CRP and procalcitonin were helpful in differentiation of CNS infection and specifically bacterial meningitis from other disorders. 22 , 31 , 32 However, these studies were not performed in the whole population of patients with suspected CNS infection and did not include patients with systemic infections without CNS involvement, where acute phase reactants are also elevated. Our results indicate that inflammatory markers in blood have a limited diagnostic value in the diagnosis of CNS infection and these cannot be used to exclude this.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in the differentiation of bacterial from viral meningitis, PCT has shown promise in multiple studies with sensitivities ranging from 70% to 100% and specificity ranging from 81% to 100%. [7][8][9][10][34][35][36][37] In many of these studies, PCT performed better than CRP, which had a sensitivity ranging from 70% to 86% and specificity ranging from 75% to 90%. 7,34,35 In addition, PCT has demonstrated a more consistent downtrend from the time of admission to 72 hours after starting antibiotics, while CRP did not show this pattern of change, suggesting that PCT may be superior in predicting response to therapy.…”
Section: Discussionmentioning
confidence: 99%
“… 45 When the body is infected, PCT can be rapidly produced and released into blood under the action of inflammatory factors or bacterial toxins. 46 PCT is strongly associated with APACHE II and SOFA, two important scoring systems for assessing the severity of a patient’s condition. That is, the more severe the disease, the higher the APACHE II and sofa scores, the greater the PCT value, and vice versa.…”
Section: Discussionmentioning
confidence: 99%